2005
DOI: 10.1016/j.jfa.2004.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Geometric quantization, complex structures and the coherent state transform

Abstract: It is shown that the heat operator in the Hall coherent state transform for a compact Lie group K (J. Funct. Anal. 122 (1994) 103-151) is related with a Hermitian connection associated to a natural one-parameter family of complex structures on T * K. The unitary parallel transport of this connection establishes the equivalence of (geometric) quantizations of T * K for different choices of complex structures within the given family. In particular, these results establish a link between coherent state transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 13 publications
3
54
0
Order By: Relevance
“…In [Hal02, FMMN05,FMMN06], it was shown that the CST can be understood in terms of the geometric quantizations of T * K arising from the vertical and Kähler polarizations. Indeed, one has the isomorphism of Hilbert spaces…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [Hal02, FMMN05,FMMN06], it was shown that the CST can be understood in terms of the geometric quantizations of T * K arising from the vertical and Kähler polarizations. Indeed, one has the isomorphism of Hilbert spaces…”
Section: Preliminariesmentioning
confidence: 99%
“…Hall computed this BKS pairing, with the following result. In [FMMN05,FMMN06], the authors considered a one-real-parameter family of polarizations connecting the vertical polarization with the Kähler polarization on T * K. The corresponding BKS pairing maps were shown to be unitary. Degenerating one of the Kähler polarizations to the vertical polarization, one recovers Hall's result relating the BKS pairing with the CST.…”
Section: Preliminariesmentioning
confidence: 99%
“…In [FMMN05,FMMN06], Florentino-Mattias-Mourão-Nunes looked at the results of [Hal02a] in terms of the one-parameter family of complex structures described above, namely those obtained from the adapted complex structure by scaling in the fibers. Using ideas similar to the ones in [ADW91], these authors consider a parallel transport in the Hilbert bundle associated to the family of complex structures.…”
Section: Connections To Geometric Quantizationmentioning
confidence: 99%
“…For example, this way of thinking provides a simple explanation for the formula expressing the adapted complex structure in terms of Jacobi fields (Section 3.3), and sheds light on the results of [FMMN05,FMMN06] (Section 3.4). We also hope that, as suggested by Thiemann, the use of other imaginary-time Hamiltonian flows will lead to the construction of new complex structures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation